An NP-movement Account of Tough Constructions - Reider, Michael (Kansas Working Papers in Linguistics, 1996)
Chomsky’s (1981) wh-movement analysis of tough constructions is inadequate when tough subjects involving internal [theta]-relations are considered–unless, as Jones (1983) observes, generalized transformations, abandoned long ago, are now reintroduced in the Government-Binding (GB) framework. To replace Chomsky’s solution and thereby to obviate the need for generalized transformations in GB theory, an alternative analysis is proposed in this paper in which the tough subject originates as an embedded object, is subsequently reanalyzed as the complement of a derived adjective, and finally undergoes NP-movement to subject position. It is shown that this analysis accounts for a wide range of data, including tough constructions exhibiting wh-island effects and tough constructions containing a parasitic gap. If the solution advocated here is correct, then it must be concluded that the reintroduction of generalized transformations is simply not motivated in the case of these constructions.